2016
DOI: 10.25071/1920-7336.40285
|View full text |Cite
|
Sign up to set email alerts
|

Tragic and Heroic Moments in the Lives of Forced Migrants: Memories of Political Asylum-Seekers in Post-Apartheid South Africa

Abstract: This article examines the memories of a group of Cameroonian asylum-seekers in South Africa, analyzing personal accounts of memories of fear, suffering, and pain as well as resilience and heroism during their forced migration. The article argues that the legitimacy of applications for asylum often depends on accurate and consistent memories of specific life-threatening episodes at home and during migration. Drawing on theoretical conceptions such as construction of memory, autobiographical memory, and politics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Albeit having multiple adverse life experiences, many refugee participants keep hope for change in their lives. This was observed in the narratives produced by participants in five studies (59,64,73,76,85). However, the tendency to be courageous and resilient was more visible in children and young adults than in elderly refugees (85).…”
Section: Optimismmentioning
confidence: 89%
See 4 more Smart Citations
“…Albeit having multiple adverse life experiences, many refugee participants keep hope for change in their lives. This was observed in the narratives produced by participants in five studies (59,64,73,76,85). However, the tendency to be courageous and resilient was more visible in children and young adults than in elderly refugees (85).…”
Section: Optimismmentioning
confidence: 89%
“…We found that different methods were used in the selected studies. Narrative interviews were the most frequently used method; twelve out of 22 studies utilizing this method (58,59,62,63,65,72,73,75,76,79,80,85). In these studies, participants were asked to recall the days before migration, and describe the genocide or conflict they witnessed during their migration journey and/or after resettling in the host country.…”
Section: Memory Activation Methodsmentioning
confidence: 99%
See 3 more Smart Citations